Preliminary Study On The Mechanical Properties Of Polypropylene Rice Husk Composites - Mustapa, Mohd. Shahril Ezuan; Hassan, Azman; Rahmat, Abdul Razak (2005)
The interest in the utilization of rice husk as fillers in thermoplastics has increased recently mainly due to the needs in overcoming the environmental problems caused by agricultural by-product. This paper reports on the effects of coupling agent and impact modifier on the mechanical properties of polypropylene rice husk composites. Ethylene 1-octene copolymers (EOC) and maleic anhydride grafted polypropylene (MaPP) were used in this study as the impact modifier and coupling agent, respectively. These compounds were melt blended using twin screw extruder and then injection molded into standard test samples. Improvement of 35% in flexural strength was observed with the addition of 4 wt% of MaPP into the composites with 30 wt% rice husk. Incorporation of 20 wt% of EOC in the composites has also shown significant enhancement in the impact properties of the blends but reduced the flexural modulus.